Application Palm Oil Waste by Different Concentrate of Gill Morphology Damage and Survival Rate of Snake Skin Gourami (Trichogaster trichopterus Blkr) - Yusron Al Anshory Harahap; Saberina Hasibuan; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted from Desember 2014 to January 2015 at Water quality Management laboratory Fisheris and Marine Science Faqulty of Riau University. The aim of the research was to investigate the effect Palm oil waste by different concentrate of damage gill and survival rate of snake skin gourami (Trichogaster trichopterus Blkr). Experimental method was applied in the research with five treatments and three replications. The treatment in the research was application palm oil waste with concentration of P0 : Without palm oil waste (control), P1: 1,286 ml/L, P2: 12,86 ml/L, P3: 25,72 ml/L and P4: 38,58 ml/L. The result showed the change of gill morphology structure of snake skin gourami (Trichogaster trichopterus Blkr). Changing on gill morphology showed the damage using palm oil waste 1,286 ml/L by survival rate 46,6 %. Changing on gill morphology structure indicate the damage is begun from hipertropy, poliferasi sel, hyperplasia, degenerasy and nekrosis. Meanwhile supreme gill morphology damage is occured on application palm oil waste 38,58 ml/L and the lowest survival rate of 26, 6%.Keyword : Tricogaster trichopterus, Palm oil waste, hypertrofi, hyperplasia, nekrosis, degeneracy